Ultra Brief Psychological Interventions for COVID-19 Pandemic: Introduction of a Locally-Adapted Brief Intervention for Mental Health and Psychosocial Support Service - Nicholas Pang Tze Ping; Wendy Diana Shoesmith; Sandi James; Noor Melissa Nor Hadi; Eugene Koh Boon Yau; Loo Jiann Lin (2020)
The ultra-brief psychological interventions (UBPI) was created in 2018 to empower healthcare providers with psychological skills that can be delivered within a short period. Techniques used within UBPI were adopted from a variety of well established psychotherapies and distilled into its core essentials. This enabled practitioners of UBPI to deliver specific psychological skills in the appropriate context to the client within a period of 15–20 min. UBPI was also manualised to standardised training of practitioners. During the novel coronavirus disease of 2019 (COVID-19) pandemic, UBPI was modified to suit the unique psychological demands of the pandemic. This article presents how UBPI was adapted and used with healthcare providers dealing with COVID-19 and also with the public who required psychological first aid (PFA).